2011
DOI: 10.1111/j.1523-536x.2010.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Rate of Cervical Dilation in Nulliparous Women at Term

Abstract: In our setting, the rate of labor in nulliparous women at term was highly variable, and it did not appear to be affected by cervical dilation on admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…The combined effect of these biases probably explains in part their finding that the rate of active-phase dilatation increases exponentially, rather than linearly as Friedman and many others have previously found. [6][7][8][9][10][25][26][27][28][29][30][31][35][36][37][38][39][40][41][42][43][44][45][46] Transition to active phase One critically important way in which the new guidelines depart from the old is in identifying the transition from latent to active phase during the first stage. It is widely, but erroneously, concluded from the Friedman dilatation curve that the active phase of labor begins at 4 cm.…”
Section: Analytical Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined effect of these biases probably explains in part their finding that the rate of active-phase dilatation increases exponentially, rather than linearly as Friedman and many others have previously found. [6][7][8][9][10][25][26][27][28][29][30][31][35][36][37][38][39][40][41][42][43][44][45][46] Transition to active phase One critically important way in which the new guidelines depart from the old is in identifying the transition from latent to active phase during the first stage. It is widely, but erroneously, concluded from the Friedman dilatation curve that the active phase of labor begins at 4 cm.…”
Section: Analytical Issuesmentioning
confidence: 99%
“…In fact, numerous studies done in different parts of the world over the course of several decades confirmed the basic nature of the original curves, and validated their usefulness in clinical practice. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] There have been disagreements over the importance of the latent phase or even the existence of the deceleration phase of dilatation, but the core finding that active-phase cervical dilatation progresses linearly, with a lower limit of normal approximately 1.0 cm/h in nulliparas, has been remarkably consistent among studies. It is also noteworthy that in many institutions the introduction of labor curves to clinical care was associated with a decline in the cesarean rate.…”
Section: Misconceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, receiving oxytocin at an earlier stage of labor is associated with a higher cesarean risk (5). The cesarean rate following early labor admission in this low-risk population is reported to be more than twice as high as the reference group rate in most studies (15) although an Italian team recently reported no difference in cesarean rates between women presenting at ≤ 4 cm or > 4 cm (35). Cesareans for dystocia were higher in the early admission groups in both identified studies reporting specific surgical indications (p < 0.001 in each study) (1,4).…”
Section: The Partographmentioning
confidence: 78%
“…Women admitted early (e.g., < 4 cm dilatation) are approximately twice as likely to be augmented with oxytocin when compared to women admitted in more active labor (1,2,34). Indeed, the rate of oxytocin use is inversely related to cervical dilatation at admission (r = −0.79, p < 0.05) (35). Moreover, receiving oxytocin at an earlier stage of labor is associated with a higher cesarean risk (5).…”
Section: The Partographmentioning
confidence: 99%